A Critical Period for the Rapid Modification of Synaptic Properties at the VPm Relay Synapse - Pan, Libiao; Yang, Junhua; Yang, Qian; Wang, Xiaomeng; Zhu, Liya; Liu, Yali; Lou, Huifang; Xu, Chou; Shen, Ying; Wang, Hao (Frontiers in Molecular Neuroscience, 2017)
In addition to cortical areas, the thalamus also displays plasticity during a critical period in early life. Since most sensory information is transmitted to the cortex via the thalamus, it will be of significant interest to understand the precise time window and underlying mechanisms of this critical period in the thalamus. By using in vitro whole-cell patch recording in acute brain slices, we found that VPm relay synapses were only sensitive to whisker deprivation from postnatal day 11 (P11) to P14. Whisker deprivation initiated within the P11 to P14 window significantly reduced the amplitude of AMPAR-EPSCs, but not NMDAR-EPSCs when recorded 24 hours after whisker removal. From P10 to P11, the timing for entry into the critical period and the kinetics underlying NMDAR-EPSCs function were significantly altered. At P11, NMDAR-EPSCs were less sensitive to ifenprodil, a selective blocker of NR2B-containing NMDAR, and the protein level of NR2A was significantly increased compared to those at P10. At the end of the critical period there were no obvious changes in synaptic properties when compared between P14 and P15. Using calcium imaging, we found that fewer P15 VPm neurons could be excited by the GABAa receptor agonist, muscimol, when compared to P14 VPm neurons; this correlated to an increase in KCC2 expression. Our studies revealed a precise critical period of sensory experience-dependent plasticity in the thalamus featuring distinct molecular mechanisms which occur at the start and end of this critical window.